Why Special Issue of NJOG? - Baral, Gehanath; Dangal, Ganesh (Nepal Journal of Obstetrics and Gynaecology, 2018)
Additional issue is published on the occasion of ISOFS 2018 conference in Kathmandu. This is a unique practice this time in publication cycle because of the important women’s health issue – the obstetric fistula.